2014
DOI: 10.1260/0144-5987.32.6.989
|View full text |Cite
|
Sign up to set email alerts
|

An Energy Efficiency Analysis of an Industrial Reheating Furnace and an Implementation of Efficiency Enhancements Methods

Abstract: Rapid consumption of energy resources, increasing energy needs, the competitive conditions in the industry and environmental concerns, all of those call for efficient use of energy resources. In this context, energy efficiency studies were carried out in a rolling mill of a reheating furnace of an integrated industrial enterprise. In studies, some important efficiency measurements were conducted, mass and energy balances were established by using the results of these measurements and the operating data of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The reheating furnace and the roll mills are the target area as they are the highest energy consumers in whole process. [26,27,28] 11 Technology advances are developed for reheat furnaces all configured to reduce the consumption of thermal energy in furnaces.…”
Section: Opportunities For Energy Efficient Technologiesmentioning
confidence: 99%
“…The reheating furnace and the roll mills are the target area as they are the highest energy consumers in whole process. [26,27,28] 11 Technology advances are developed for reheat furnaces all configured to reduce the consumption of thermal energy in furnaces.…”
Section: Opportunities For Energy Efficient Technologiesmentioning
confidence: 99%
“…Recently, numerous studies have been done on heating furnace [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Relatively thorough studies were carried out on the reheating furnace by Han et al from 2007 to 2012 [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the fuel consumption reduced, and the energy efficiency increased due to the implementation of the slab preheating chamber. Moreover, several measures to improve efficiency were conducted in practice by Kilinc et al [17] including reducing excess air, preventing air leakage loss of regenerator and establishing economizer. The efficiency of the reheating furnace was raised from 61.83% to 69.43% after the implementation of energy-saving measures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort has been made around these aspects to improve their energy efficiency [12] and carbon mitigation [13]. However, today's best practice values for heating a tonne of steel to the right temperature for rolling or forging is still above 1.0 GJ/tonne [14]. If no substantial upgrading of existing combustion technologies is put in place, furnace operators will likely struggle to achieve further reduction in fuel consumption and CO 2 emission [15].…”
Section: Introductionmentioning
confidence: 99%